To subtract \( 8\sqrt{23} - \sqrt{23} \), you can combine the like terms:
\[ 8\sqrt{23} - \sqrt{23} = (8 - 1)\sqrt{23} = 7\sqrt{23} \]
So the answer is:
\[ 7\sqrt{23} \]
Therefore, the correct response is:
7√23
. (1 point)
Responses
723−−√
7 start root 23 end root
823−−√
8 start root 23 end root
746−−√
7 start root 46 end root
846−−√
1 answer
To subtract \( 8\sqrt{23} - \sqrt{23} \), you can combine the like terms:
\[ 8\sqrt{23} - \sqrt{23} = (8 - 1)\sqrt{23} = 7\sqrt{23} \]
So the answer is:
\[ 7\sqrt{23} \]
Therefore, the correct response is:
7√23